Childhood trauma and treatment outcomes in short-term psychodynamic and cognitive behavioral therapy for adult depression - Malkomsen, Anders; Ulberg, Randi; Dammen, Toril; Evensen, Julie Horgen; Hummelen, Benjamin; Løvgren, André; Osnes, Kåre; Wilberg, Theresa; Røssberg, Jan Ivar (Frontiers in Psychiatry, 2025)
Childhood trauma (CT) is a known risk factor for major depressive disorder (MDD), yet its implications for treatment selection remain unclear. This exploratory randomized controlled trial (N = 100) compared short-term psychodynamic psychotherapy (STPP) and cognitive behavioral therapy (CBT) in adults with MDD treated in outpatient clinics. CT was assessed with the Childhood Trauma Questionnaire–Short Form (CTQ-SF), and depressive symptoms were measured using the Beck Depression Inventory-II (BDI-II) and the Hamilton Depression Rating Scale (HDRS) at baseline and after 28 weeks of therapy. Linear mixed-model analyses showed that CT was associated with higher depression severity at the start of treatment. No significant predictive effects of CT were found for treatment outcome or for moderation of the comparative effectiveness of CBT and STPP. Emotional abuse was initially associated with greater improvement in STPP compared to CBT on the HDRS, but the effect did not remain significant after correction for multiple testing. These findings suggest that both CBT and STPP are suitable options for patients with MDD and a history of CT.